(untitled) (Journal of Imam Al-Kadhim College, 2023)
Abstract: Ibn Ishaq relied on a group of narrators who transmitted the historical news about the childhood of the Prophet Muhammad (peace and blessings of God be upon him and his family). As a result, the totality of his narrations was few and had something of a miraculous nature, as if they were influenced by the system of holiness and the attention to its ideas or to make the narrations more acceptable in Islamic thought, as they talk about the Prophet of Islam Muhammad (peace and blessings of God be upon him and his family), so do you think that Muhammad ibn Ishaq provided all his information The historical narrative that he received from its primary sources, namely, the narrators from among the sons of the Companions and the Followers, or he endeavored to coordinate what he heard and presented his information in a concise manner, or he was unable to provide historical narratives capable of diagnosing the childhood of the Prophet Muhammad (peace and blessings of God be upon him and his family) in all its details, so a historical narrative appeared that simulates The nature of childhood, and since it belongs to the Seal of the Prophets, he made for it a sacred idea that takes care of its apparent embodiment, on which human thought can focus if it reaches the nature of the sacred phenomenon of the marital relationship that took place between the Prophet’s parents and then his birth and breastfeeding. His news, which he wrote down in the Book of Al-Sir and Al-Maghazi, was a nucleus for authenticating the news of the Prophet’s biography, to be approved by the Abbasid authority, and then became the main reference for everyone who wrote or transmitted the news of the era of the message. Birth and then the hour of the parents meeting to be a reason for the birth of the Prophet and then his upbringing and breastfeeding in the desert of Bani Saad.